Pediatric Malignant Arrhythmias Caused by Rare Homozygous Genetic Variants in TRDN: A Comprehensive Interpretation - Sarquella-Brugada, Georgia; Fernandez-Falgueras, Anna; Cesar, Sergi; Arbelo, Elena; Jordà, Paloma; García-Álvarez, Ana; Cruzalegui, Jose Carlos; Merchan, Erika Fernanda; Fiol, Victoria; Brugada, Josep; Brugada, Ramon; Campuzano, Oscar (Frontiers in Pediatrics, 2021)
Aim. To perform a comprehensive phenotype-genotype correlation of all rare variants in Triadin leading to malignant arrhythmias in pediatrics. Methods. Triadin knockout syndrome is a rare entity reported in pediatric population. This syndrome is caused by rare variants in the TRDN gene. Malignant ventricular arrhythmias and sudden cardiac death can be a primary manifestation of disease. Although pharmacological measures are effective, some patients require an implantable defibrillator due to high risk of arrhythmogenic episodes. Main Results. Fourteen rare genetic alterations in TRDN have been reported to date. All of these potentially pathogenic alterations are located in a specific area of TRDN, highlighting this hot spot as an arrhythmogenic gene region. Conclusions. Early recognition and comprehensive interpretation of alterations in Triadin are crucial to adopt preventive measures and avoid malignant arrhythmogenic episodes in pediatric population.